Acute effect of iloprost inhalation on right atrial function and ventricular dyssynchrony in patients with pulmonary artery hypertension. Issue 1 (14th October 2016) - Gabrielli, Luigi; Ocaranza, María Paz; Sitges, Marta; Kanacri, Andrés; Saavedra, Rodrigo; Sepulveda, Pablo; Sepulveda, Luis; Rossel, Victor; Zagolin, Monica; Verdejo, Hugo E.; Baraona, Fernando; Zalaquett, Ricardo; et al.
Abstract : Background: Right atrium function and ventricular function have significant prognostic value in pulmonary arterial hypertension patients. Acute changes in right ventricular synchrony and right atrium function postiloprost inhalation have not been evaluated. Methods: Cross‐sectional study. Consecutive pulmonary arterial hypertension patients (group I from Nice classification) were included. Echocardiographic right atrium and right ventricular function pre‐ and postiloprost inhalation, including a right ventricular dyssynchrony index and right atrium function using speckle tracking, were performed in all patients. Results: Twenty pulmonary arterial hypertension patients, 44±7 years and 90% females, were included. After iloprost inhalation, we observed a significant increment in right ventricular fractional area change and a significant decrease in right ventricular dyssynchrony index (21.4±5.6% vs 26.1±4.0 %, P =.007 and 79±44 vs 32±22 mseconds, P <.01, respectively), also an improvement in right atrium reservoir function (8.6±3.1% vs 11.7±3.5 %, P =.002). Conclusions: Iloprost inhalation induces acute changes in right ventricular function, dyssynchrony, and right atrium performance that may add relevant clinical information in the management and risk stratification of pulmonary arterial hypertension patients.